2006
DOI: 10.1534/genetics.104.036905
|View full text |Cite
|
Sign up to set email alerts
|

The Absence of Top3 Reveals an Interaction Between the Sgs1 and Pif1 DNA Helicases inSaccharomyces cerevisiae

Abstract: RecQ DNA helicases and Topo III topoisomerases have conserved genetic, physical, and functional interactions that are consistent with a model in which RecQ creates a recombination-dependent substrate that is resolved by Topo III. The phenotype associated with Topo III loss suggests that accumulation of a RecQ-created substrate is detrimental. In yeast, mutation of the TOP3 gene encoding Topo III causes pleiotropic defects that are suppressed by deletion of the RecQ homolog Sgs1. We searched for gene dosage sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
54
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 88 publications
2
54
0
Order By: Relevance
“…Although Scrrm3⌬ cells do not exhibit changes in GCR or mitochondrial genome stability, these cells do exhibit genetic instability, presumably due to replication fork pausing at specific chromosomal loci, such as the ribosomal DNA locus (31,32,45,59,68,69). ScRRM3 and ScPIF1 exhibit genetic interactions (including synthetic lethality) with many gene products required in DNA replication and S-phase checkpoint arrest (1,2,17,50,58,59,69,71). Thus, additional inactivation of other DNA helicases involved in DNA replication or repair or proteins essential for the S-phase checkpoint may yet reveal an interesting phenotype in mPif Ϫ/Ϫ animals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although Scrrm3⌬ cells do not exhibit changes in GCR or mitochondrial genome stability, these cells do exhibit genetic instability, presumably due to replication fork pausing at specific chromosomal loci, such as the ribosomal DNA locus (31,32,45,59,68,69). ScRRM3 and ScPIF1 exhibit genetic interactions (including synthetic lethality) with many gene products required in DNA replication and S-phase checkpoint arrest (1,2,17,50,58,59,69,71). Thus, additional inactivation of other DNA helicases involved in DNA replication or repair or proteins essential for the S-phase checkpoint may yet reveal an interesting phenotype in mPif Ϫ/Ϫ animals.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of nuclear ScPif1, gross chromosomal rearrangements are in-creased, and healing of broken ends via telomere addition is more frequent (42,47,48,61). Nuclear ScPif1 is also essential for mitigating the deregulated activity of the RecQ helicase Sgs1 observed in top3⌬ cells (71). Interestingly, ScPif1 (but not Rrm3) colocalizes almost exclusively with Rad52 in nuclei and is recruited to discrete foci after DNA damage (71).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that Pif1, together with DNA polymerase d, helps generate flaps from the 59 ends of Okazaki fragments (Ryu et al 2004;Budd et al 2006;Boule and Zakian 2007;Rossi et al 2008;Stith et al 2008). Pif1 also counteracts Sgs1 DNA helicase activity, promoting survival in the absence of the Top3 topoisomerase (Wagner et al 2006), and may also play a role in preventing genomic instability caused by G-quadruplex-forming sequences (Ribeyre et al 2009).…”
mentioning
confidence: 99%
“…The fact that the observed decrease in survival was not specific to the lack of a single type of topoisomerase can be explained by the fact that topoisomerase complexes at a DNA lesion may alter the repair efficiency and initiate alternative and more efficient processing of damage repair. 60,61 Moreover, the deletion of TOP1 has no effect on yeast survival, 62 furthermore, it is possible to conclude that the toxic mechanism of nor-β-lapachone and its derivatives does not include topoisomerase I poisoning. Also, our results indicate that topoisomerases served as important survival factors following DNA damage induced by the tested compounds.…”
mentioning
confidence: 99%